Application of Intelligent Three-state Pang-Pang Control to Heat Exchange Station - Wen Biao Wang; Yong Sun; Si Yuan Wang; Han Wen (Institute of Advanced Engineering and Science, 2014)
The heat exchange station of central heating system has been increasingly widely used as the intermediate hub connecting the heat source and heat users. If the specific temperature control requirements are not satisfied effectively and specifically, the security and stability of the primary network and quality of the secondary network will be affected directly. A temperature control scheme of the heat exchange station is presented based on intelligent three-states Pang-Pang. On the basis of mechanism analysis, we choose the average of supply and return water temperatures of secondary network as the controlled variable in presented temperature control scheme, which is equivalent to inducing the supply water temperature as the feedforward signal. The advantages of the intelligent three-state Pang-Pang control algorithm lie in improving the stability of the primary network, reducing the overshoot and accelerating the response of the secondary network. The application of the presented control scheme to the practical engineering shows that it not only implements the automatic control of the temperature of heat exchange station hence improves its control performance but also enhances and improves the controllability of the system effectively and especially has the referential and extending significance for heat exchange station transforming open-loop to closed-loop control. DOI : http://dx.doi.org/10.11591/telkomnika.v12i5.3538